The Impact of Cross-National Carriers of Business Ethics on Attitudes about Questionable Practices and Form of Moral Reasoning - Husted, Bryan W.; Dozier, Janelle Brinker; McMahon, J. Timothy; Kattan, Michael W. (Journal of International Business Studies, 1996)
The study explores the impact of cross-national carriers of ethics on attitudes about questionable business practices and form of moral reasoning across Mexican, Spanish and U.S. MBAs. Results show substantial agreement across cultures on twelve personally most objectionable practices, while form of moral reasoning varied significantly. Social cognitive theory is used to address the theoretical and practical implications.